Dilemma of bumiputera contractor / Zubir Sayuti - Sayuti, Zubir (Faculty of Civil Engineering, 2007)
Dilemma of bumiputera contractor is referring the problem that their faced in construction industries. Each year, the number of contractor is increasing but the government projects still remain at the same quantities or become lesser than the previous year. This will give a big competition among them. Besides that, other project has been closed such as Scenic Bridge at Johor where connecting our country to Singapore. That was giving a big impact to bumiputera contractor. This research will discover about the problem of bumiputera contractor in construction industry other than less government tender and too many contractors. It will show the relationship about the current issues with the problems. Besides that, it also discovers the solutions or recommendation to solve the problems. Finally, we will knew what is the main problems of bumiputera contractor in construction industry and the solutions (recommendations) to solve the problem. Keyword: Bumiputera contractors, government project, construction, problem,